Phycocyanin Stabilized Chitosan Nanoparticles Loaded Cephalothin-Bacteriocin Nano Drug Conjugate Preparation for the Enhanced Antibacterial Activity, Controlled Drug Release and Biocompatibility (Asian Journal of Pharmaceutics (AJP), 2016)
Aim: The aim of the present work is to evaluate improved or enhanced antibacterial activity, controlled drug release, and biocompatibility of bacteriocin - chitosan nanoparticles (NPs) -cephalothin nano drug conjugate formulation stabilized by phycocyanin. Materials and Methods: Ionic gelation method was carried out to synthesize phycocyanin stabilized nano drug conjugate, and the synthesized nano drug conjugate was characterized by electron microscopy for determination of particle size and shape, energy dispersive atomic X-ray spectroscopy for elemental composition and surface modification by Fourier transform infrared spectroscopy. Antibacterial activity was studied by well diffusion assay, microdillution colorimetric assay, and biofilm inhibition assay against food spoilage pathogenic bacterial strains. In vitro drug release of cephalothin from the nano drug, conjugate preparation was done by continuous dialysis method. Effect of temperature on the antibacterial activity of nano drug conjugate was also studied biocompatibility of nano drug conjugate was evaluated using in vitro 3-(4, 5-dimethyl thiazol-2-yl)-2-5-dephenyl tetrazoliumbromide (MTT) cyctotoxicty test using vero cell line. Hemocompatibility of nano drug conjugate was studied by spectrophotometric determination of plasma hemoglobin (Hb) and hemolysis of nano drug conjugate treated blood. Results and Discussion: Nano drug conjugate synthesized by ionic gelation method revealed electron-dense core-shell spherical particles with nano size range. An increase in antibacterial activity against the tested bacterial strains was recorded in nano drug conjugate-bacteriocin preparation treatment studied by all the assays which revealed an effective synergistic activity and the activity was not affected under the influence of temperature except 70Â°C. Nanoformulation brought about a steady constant release of cephalothin at increasing time. Less cytotoxic effect of nano drug conjugate against vero cell line adopting MTT assay and changes on plasma Hb and hemolysis supported the biocompatibility. Hemocompatibility of nano drug conjugate revealed no distinct changes in plasma Hb and complete absence of hemolysis. Conclusion: Formulation of cephalothin-bacteriocin by the phycocyanin stabilized chitosan NPs preparation showed distinct antibacterial activity, controlled release pattern, and best biocompatibility. This study would suggest the possible utilization of the synthesized nano drug conjugate against pathogenic bacterial strains.